Superstition, conspicuous spending, and housing market: Evidence from Singapore - HE, Jia (Institutional Knowledge at Singapore Management University, 2020)
We study the effect of superstition and conspicuous spending motives on housing demand and price in Singapore. We find that buyers pay less for homes with unlucky addresses and more for homes with lucky addresses. There were fewer housing transactions on inauspicious days of the lunar calendar when people are advised to avoid making major economic decisions. This suggests that superstitious belief still affects economic activities. The demand for lucky addresses is also weaker on these inauspicious days, suggesting that superstitious belief indeed affects the demand for lucky addresses. Moreover, the price premium for a lucky address is significantly higher for apartments of larger size or on top floors. Because these two housing features can signal wealth and are highly visible, the larger price premium suggests that conspicuous spending motives also play a significant role in the Singapore housing market. We also find that informed buyers, even with less superstitious or conspicuous spending motives, might still pay price premiums for lucky addresses. In contrast, uninformed buyers are unlikely to pay a premium for these addresses.